Pearls of the Deep - Hrabal, Bohumil 1914-1997 (Second Run, 2023)
Gathering five seminal figures of the Czech New Wave at the dawn of their careers for the first celluloid transliteration of Bohumil Hrabal, "Pearls of the Deep" has cultural and historical cachet to burn, but as with most omnibus films the on-screen results are mixed. Indispensable if you're interested in the development of contemporary Czech film; for anyone else, the first and last segments just about make it worth the price of a rental. The opening "The Death of Mr. Baltazar", about a gearhead couple's trip to the road races with an aged parent, shows the young Menzel already wielding the offhand wit, attention to detail and sure grasp of the tragicomic Hrabalasian cosmos that would characterize his later collaborations with the author. In Němec's austere "The Impostors" two old men while away their hospital days trading stories of their brilliant careers until a predictable shaggy-dog ending. Schorm's colorful "House of Joy", in which two insurance agents try to sell a policy to an eccentric rural artist, has its moments but rather overplays its absurdist hand. Chytilová's "The Globe Buffet", chronicling a wedding party at a gritty cafeteria, contains some striking images but, foreshadowing her subsequent "Daisies", it's a bit too mannered and self-conscious to register emotionally. In almost rebuking contrast is Jireš's Romance, an affectionate, sweetly funny sketch of a boy's infatuation with a fetching Roma girl that heralds the then-new Czech cinema at its most understatedly sublime. [prague.tv]
Original: Tschechoslowakei 1966
Bildformat: 16:9 (1,37:1)
Extras: 1 Beiheft
Keywords: Film; Blu-Ray-Disc